Totto Chan External Conflict in The Novel Tetsuko Kuroyanagi Totto Chan The Little Girl at The Window - Helmita Helmita; Haqi Farma (Jurnal Ilmiah Langue and Parole, 2023)
This research is motivated by the existence of Totto-chan's external conflict which is realized by the author in the work of Totto Chan the Little Girl at the Window by Tetsuko Kuroyanagi. The purpose of this study is to identify the external conflict experienced by Totto-chan, as well as the causes of the conflict in the novel Totto Chan the Little Girl at the Window by Tetsuko Kuroyanagi. In this research the researcher used Structural Analysis theory by Tzvetan Todorov. The method used in this research is descriptive qualitative. The data in this novel are quotes from words, sentences related to the external conflict experienced by the character Totto-Chan. Data collection techniques in this study were reading, marking data and recording data related to external conflicts in the novel Totto Chan the Little Girl at the Window by Tetsuko Kuroyanagi. The results of this study indicate that in the novel Totto Chan the Little Girl at the Window by Tetsuko Kuroyanagi, the external conflict experienced by Totto-chan is caused by Totto-chan's hyperactive nature which often causes a lot of problems because Totto can't stop moving, causing a lot of stress people are annoyed by it and also Totto's imagination is too high which makes it difficult for Totto to understand the circumstances around her and she always does the things she likes without thinking about the consequences of her actions.